POLITICAL ECONOMY OF ECO-SUSTAINABLE ALTERNATIVES progressive and equitable futures. - Westra, Richard, 1954- (ROUTLEDGE, 2026)
Westra recounts how the unceremonious collapse of Soviet-style socialism, coupled with mounting awareness of unfolding environmental destruction and irreversible climate change opened the door to a new, wide-ranging, social change literature. In this exciting book, he begins by tracing out the case for the Anthropocene. He then provides an unparalleled, inclusive critical exploration of the plurality of progressive designs on offer. These include the Green New Deal, "nowtopias" of cooperative, solidarity and commoning economies, ecofeminism, Degrowth society as well as ecosocialism and democratic socialism.Westra firstly explains why the Green New Deal program to sustainably develop capitalism is unworkable given the boundedness of resources necessary to generalize the advanced economy "way of life" it seeks to maintain. Secondly, while he concurs with much that the new social change literature offers, his concern is with the way it abandons a major caution that had been leveled at so-called "utopian socialists" in the past. To be sure, the problem does not reside with bursts of creative, future-directed thinking in themselves. Rather, where difficulties arise is over the paucity of attention devoted to questions of economic coordination and principles of economic viability. Westra explains how only by combining several economic principles, each operating at a determinate scale and devoted to specific elements of human social and material reproduction, will the promise of an equitable, eco-sustainable human future be realized.This unique volume will be of interest to academic specialists and students of political economy, economics, environmental sustainability, sociology and political science. Progressive policymakers and social activists will also find its arguments refreshing and compelling.